Coactivation of Tie2 and Wnt signaling using an antibody–R-spondin fusion potentiates therapeutic angiogenesis and vessel stabilization in hindlimb ischemia - Byungtae Hwang; Min-Young Jeon; Ju-Hong Jang; Young-Lai Cho; Dong Gwang Lee; Jeong-Ki Min; Jangwook Lee; Jong-Gil Park; Ji-Hun Noh; Wonjun Yang; Nam-Kyung Lee (mAbs)
Therapeutic angiogenesis by intentional formation of blood vessels is essential for treating various ischemic diseases, including limb ischemia. Because Wnt/β-catenin and angiopoietin-1/Tie2 signaling play important roles in endothelial survival and vascular stability, coactivation of these signaling pathways can potentially achieve therapeutic angiogenesis. In this study, we developed a bifunctional antibody fusion, consisting of a Tie2-agonistic antibody and the Furin domains of R-spondin 3 (RSPO3), to simultaneously activate Tie2 and Wnt/β-catenin signaling. We identified a Tie2-agonistic antibody T11 that cross-reacted with the extracellular domain of human and mouse Tie2, and evaluated its ability to increase endothelial cell survival and tube formation. We generated a bifunctional T11–RF12 by fusing T11 with the Furin-1 and −2 domains of RSPO3. T11–RF12 could bind not only to Tie2, but also to LGR5 and ZNRF3, which are counterparts of the Furin-1 and −2 domains. T11–RF12 significantly increased Wnt/β-catenin signaling, as well as the formation of capillary-like endothelial tubes, regardless of the presence of Wnt ligands. Coactivation of Tie2 and Wnt/β-catenin signaling by T11–RF12 increased the blood flow, and thereby reduced foot necrosis in a mouse hindlimb ischemia model. In particular, T11–RF12 induced therapeutic angiogenesis by promoting vessel stabilization through pericyte coverage and retaining endothelial expression of Frizzled 10 and active β-catenin. These results indicate that the agonistic synergism of Tie2 and Wnt/β-catenin signaling achieved using T11–RF12 is a novel therapeutic option with potential for treating limb ischemia and other ischemic diseases.